2012
DOI: 10.1088/0022-3727/45/32/325201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticles on an rf discharge afterglow

Abstract: The influence of nanoparticles on a discharge plasma afterglow in argon is studied using particle-in-cell Monte Carlo collision simulations. The anomalous electron density increase observed in the experiment (Berndt et al 2006 Plasma Sources Sci. Technol. 15 18) is analysed on the basis of the electron and ion distribution functions. It is shown that the departure of fast electrons to the electrodes in the early afterglow is responsible for the rapid increase in the electron density. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Schweigert and Alexandrov [66] and Alexandrov et al [67] performed particle-in-cell (PIC) Monte Carlo collision (MCC) simulations to study the influence of nanoparticles on an argon plasma afterglow under conditions similar to the experiments by Berndt et al [52]. Using the simulated ion and electron energy distribution functions (IEDF and EEDF, respectively), Schweigert and Alexandrov [66] and Alexandrov et al [67] have shown that the loss of fast electrons to the electrode in the early afterglow (diffusion cooling) leads to a change of the electron and ion currents on the dust particle surfaces and a drop of the dust floating potential. Alexandrov et al [67] reported that the main production of desorbed electrons occurs during this electron cooling phase (30-50 μs into the afterglow).…”
Section: Influence Of Dust On Plasma Decaymentioning
confidence: 99%
“…Schweigert and Alexandrov [66] and Alexandrov et al [67] performed particle-in-cell (PIC) Monte Carlo collision (MCC) simulations to study the influence of nanoparticles on an argon plasma afterglow under conditions similar to the experiments by Berndt et al [52]. Using the simulated ion and electron energy distribution functions (IEDF and EEDF, respectively), Schweigert and Alexandrov [66] and Alexandrov et al [67] have shown that the loss of fast electrons to the electrode in the early afterglow (diffusion cooling) leads to a change of the electron and ion currents on the dust particle surfaces and a drop of the dust floating potential. Alexandrov et al [67] reported that the main production of desorbed electrons occurs during this electron cooling phase (30-50 μs into the afterglow).…”
Section: Influence Of Dust On Plasma Decaymentioning
confidence: 99%
“…As shown experimentally in (Berndt et al 2006), application of the RF field can decrease the n e in dusty plasma by many times. The specific nature of this effect, which is being debated (Schweigert & Alexandrov 2012), is not important for our discussion. What is important, however, is that the effect is local and much stronger than that caused by ponderomotive expulsion (Zheng 1990).…”
Section: Rf Emission Mechanismmentioning
confidence: 99%
“…The dust charge in the glow regime may be found assuming an equal flux of ions and electrons to its surface. This approach also allows to estimate the dust charge in the afterglow plasma [24].…”
Section: Dust Charge and Forces Affecting A Dust Particlementioning
confidence: 99%
“…Plasma inhomogeneity effects and dust motion were taken into account in the models of Schweigert and Alexandrov [24] and Kravchenko et al [25], where dusty plasma afterglows were studied using PIC-MCC simulations. In [26], the behavior of a nanodusty plasma afterglow was examined, using a sectional model and also accounting for the plasma inhomogeneity and the transport of dust particles due to the effect of different forces.…”
Section: Introductionmentioning
confidence: 99%